Um estudo sobre o fenômeno do bullying entre adolescentes sob o olhar da psicologia analítica - Ulisses, Sofia Marques Viana (2019)
Bullying amongst adolescents at school shows the complexity of individual and collective psychodynamics permeated by the reproduction of violence. Despite a broad theoretical-clinical field of study about this phenomenon and its consequences, few studies have focused on an in-depth approach according to adolescents’ own views. This research aimed to investigate the phenomenon of bullying from the perspective of adolescents from the 6th to the 9th year of Elementary School attending a public school in the city of São Paulo. Therefore, through a mixed sequential method with a quantitative phase, 91 adolescents with a mean age of 13.2 years (SD = 1.20) responded to the self-report questionnaire of Forms of Bullying Scale, followed by a qualitative phase, with semi-structured interviews with eight adolescents selected from the analysis of the results of the scale. The results reveal that there is a higher frequency of students who report having observed bullying behaviors than those who reported practicing or suffering such behaviors, with frequencies of 73.6%, 49.5% and 17.6% of students involved as bystanders, victims and perpetrators, respectively. Regarding the analysis of forms of bullying, there is a greater frequency of verbal bullying in the three roles studied, which account for 80.2%, 65.9% and 41.8% of students declaring to witness, suffer or perpetrate this form of bullying. A positive correlation was observed between the victimization and perpetration factors, which was confirmed by interviews, corroborating a perspective that, instead of delineating and diagnosing the adolescents through indisputable roles, seeks to understand them dynamically. It appears that impulsive behaviors and humiliation disguised by mockery indicates the interplay between pairs marked by violence as well as arising from the expression of internal suffering and derived from family and social relations. The sometimes-conflicting dynamics expected for the adolescent trajectory, when pervaded by bullying, result in a high burden of suffering and defenses, demanding psychological care and attention. Narratives also reveal that participants demonstrated moral reasoning and empathic feelings, as well as the ability to present creative propositions of intervention and prevention of bullying in school. Such attributes require safe support and the orientation of informed adults who could guide those adolescents